Effects of Adding Unsaturated Fatty Acids on Fatty Acid Composition of Saccharomyces cerevisiae and Major Volatile Compounds in Wine - Duan, L.L.; Shi, Y.; Jiang, R.; Yang, Q.; Wang, Y.Q.; Liu, P.T.; Duan, C.Q.; Yan, G.L. (South African Journal of Enology and Viticulture, 2016)
The synergistic influences of three unsaturated fatty acids (UFAs, namely linoleic acid, oleic acid and linolenic acid) on the fatty acid composition of Saccharomyces cerevisiae and major volatile compounds were investigated in synthetic grape juice. The addition of UFAs led to a corresponding increase in UFAs in the cellular lipid, which was accompanied by a reverse reduction in the content of medium-chain saturated fatty acids (C6:0 to C14:0) and little variation in that of long-chain saturated fatty acids (C16:0 to C24:0). The supplementation of UFAs considerably improved yeast growth and fermentation activity and, in particular, increased the concentrations of most volatile compounds in wine, including higher alcohols (2-phenylethanol, 2-methyl-1-propanol and 3-(methylthio)-1-propanol), medium-chain fatty acids (butanoic acid, hexanoic acid and octanoic acid), acetate esters (isoamyl acetate and 2-phenylethyl acetate) and all ethyl esters. Remarkable linear relationships were further found between ethyl esters and the concentration of the added UFAs (R2 from 0.909 to 0.996), which significantly intensified the fruity, flowery and sweet attributes of the final wine, as assessed by calculating the odour activity values. Our results suggest that rationally increasing the concentration of UFAs is not only a practical method to improve yeast fermentation activity, but also a potential approach to manipulating wine aroma.